Enhancing access to justice in Zimbabwe: an empirical exploration of integrating socially appropriate dispute resolution to overcome barriers within the formal justice system - Maraire, Wesley (Department of Private Law, 2024)
Colonialism introduced common law in Rhodesia (now Zimbabwe). The colonial regime subsequently relegated indigenous laws, rules, and epistemologies to the status of informality, except for those that did not offend European notions of justice and morality. Despite colonial onslaughter, relegated ways of life continued guiding the majority Black population, albeit informally. This established Zimbabwe as a plural legal country. Against this background, this study explores factors impeding citizens from accessing the formal justice system, preventing them from obtaining outcomes they consider fair. Semistructured interviews with diverse legal professionals revealed a range of barriers preventing citizens from obtaining effective access to justice. Research participants identified the colonial common law system, with its emphasis on general law courts and litigation as a significant barrier to access to justice for the majority Black African population, whose traditional approaches to dispute resolution contrast with this adversarial system. Consequently, most citizens rely on non-state dispute resolution platforms that lack the force of law. This thesis also explores various ways of enhancing access to justice for citizens, including the poor and small businesses in Zimbabwe. The data revealed that the most significant solution is embracing normative conceptions of law, justice, and institutionalising socially appropriate dispute resolution processes that are culturally and geographically close to the people. Throughout the thesis, case studies, primarily from Australia and South Africa provide a comparative lens for analysing the empirical data. These countries share a history of British colonial rule and have set a path to extend access to justice to Indigenous populations, which provides a blueprint for Zimbabwe. This thesis concludes by drawing together empirical data and process theory to develop a justice system that overcomes Zimbabwe's current access to justice challenges.